2018
DOI: 10.1111/jfpp.13714
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the impact of Fusarium culmorum infection and fungicide treatment on wheat malt quality

Abstract: The objectives of this study were to investigate the impact of Fusarium culmorum infection and fungicide application on malt quality of two domestic wheat genotypes, Lucija and Osk.110/09. Wheat genotypes were subjected to four different field treatments: control/natural conditions (1), fungicide treatment (2), inoculated with F. culmorum spores and treated with fungicide (3), and inoculated with F. culmorum spores (4). Lucija was a less susceptible genotype to Fusarium infection, in contrast to Osk.110/09, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mycotoxins are retained in germ/rootlets, spent grains, and spent yeast depending on the genotype susceptibility, starting mycotoxin concentrations, and fungicide treatment [91]. Since the spectrum of found mycotoxins is so broad, as confirmed by Mastanjević et al [1], this calls for attention and updates on legislation to ensure the health of animals and, subsequently, humans.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins are retained in germ/rootlets, spent grains, and spent yeast depending on the genotype susceptibility, starting mycotoxin concentrations, and fungicide treatment [91]. Since the spectrum of found mycotoxins is so broad, as confirmed by Mastanjević et al [1], this calls for attention and updates on legislation to ensure the health of animals and, subsequently, humans.…”
Section: Discussionmentioning
confidence: 99%
“…Habschied et al (2014) [ 50 ] suggested that the infection of F. culmorum in wheat can lead to the increase in fungal proteases and activate the plants’ pathogen-related proteins, which are part of its protective strategy (KI of the infected wheat sample 51% versus 49% in control and fungicide-treated samples). Mastanjević et al (2018) [ 51 ] reached a similar conclusion in their study, suggesting that the presence of F. culmorum can even influence some of the hereditary traits of the wheat, such as grain hardness (hydrolysis of proteins adhering to the starch granules) and environment-dependent traits, including starch content (starch content decreases with the increase in Fusarium infection due to the production of amylolytic enzymes by the fungus), wet gluten content and increased water content, before and after malting compared to a non-infected sample.…”
Section: Fusarium Fungi In Brewing Cerealsmentioning
confidence: 99%